NSRG-16. LESION LOCALIZATION IN POSTERIOR FOSSA SYNDROME. Issue 2 (22nd June 2018) - Albazron, Fatimah; Bruss, Joel; Jones, Robin; Yock, Torunn; Pulsifer, Margaret; Abrams, Annah; Sato, Mariko; Boes, Aaron
Abstract: INTRODUCTION: Posterior fossa syndrome (PFS) develops in about 25% of children undergoing cerebellar tumor resection. This syndrome is characterized by mutism, ataxia, emotional lability, and behavioral changes. The exact pathogenesis of this syndrome is not well understood. OBJECTIVE: To evaluate lesion location relative to PFS development. METHODS: 203 pediatric patients who underwent cerebellar tumor resection from University of Iowa Hospitals and Clinics and Massachusetts General Hospital were evaluated for PFS through chart review. We tested for variables associated with PFS using demographics, tumor type, and lesion location. Each post-surgical lesion was manually mapped onto a template brain. Using a case-control design we compared each patient with PFS to two subjects without PFS, matched by age, gender and lesion volume. We evaluated the hypothesis that lesions of the cerebellar outflow pathway (deep nuclei and superior cerebellar peduncles) are associated with PFS. RESULTS: PFS was present in 47 of 203 subjects (23.2%). Lesions of the cerebellar outflow pathway were significantly associated with PFS development (P = 0.002). Moreover, using a novel metric of cerebellar outflow tract "lesion load", we show that the damaged proportion of cerebellar outflow is strongly associated with the rate of PFS. In addition, the rate of medulloblastoma was significantly higher in the PFS group (P = 0.035). CONCLUSION: In this large lesion mapping study we show that disruption of the cerebellar outflow pathway is significantly associated with the diagnosis of PFS. Moreover, the rates of PFS vary in accordance with the proportion of the cerebellar outflow pathway affected.